Diversity and popularity in social networks - Yann Bramoullé; Brian W. Rogers (Northwestern University, Kellogg School of Management, Center for Mathematical Studies in Economics and Management Science, 2009)
Homophily, the tendency of linked agents to have similar characteristics, is an important feature of social networks. We present a new model of network formation that allows the linking process to depend on individuals types and study the impact of such a bias on the network structure. Our main results fall into three categories: (i) we compare the distributions of intra- and inter-group links in terms of stochastic dominance, (ii) we show how, at the group level, homophily depends on the groups size and the details of the formation process, and (iii) we understand precisely the determinants of local homophily at the individual level. Especially, we find that popular individuals have more diverse networks. Our results are supported empirically in the AddHealth data looking at networks of social connections between boys and girls.
Keywords: A14; D85; I21; 330; Soziales Netzwerk; Soziale Gruppe; Homosexualität